2019
DOI: 10.1109/access.2019.2940691
|View full text |Cite
|
Sign up to set email alerts
|

The New Purity and Capacity Models for the OAM-mmWave Communication Systems Under Atmospheric Turbulence

Abstract: The orbital angular momentum (OAM) wireless communication technology is widely studied in recent literatures. But the atmospheric turbulence is rarely considered in analyzing the capacity of OAM-based millimeter wave (OAM-mmWave) communication systems. The OAM-mmWave propagated in the atmosphere environments is usually interfered by the atmospheric turbulence, resulting in the crosstalk among OAM channels, capacity degradation, etc. By taking into account the atmospheric turbulence effect, this paper proposes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…It is confirmed that in the frequency range selected in this article, a high frequency brings a large capacity of the RV communication system using the PAAR scheme in the horizontal non-Kolmogorov channel model. However, in [ 25 ], the capacity of the OAM-mmWave communication systems decreased with the increase of the transmission frequency, where the selected transmission frequency range was 100 GHz–300 GHz. We conclude that the selected transmission frequency range has a great influence on the RV communication system based on the PAAR scheme in a turbulent atmospheric environment.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…It is confirmed that in the frequency range selected in this article, a high frequency brings a large capacity of the RV communication system using the PAAR scheme in the horizontal non-Kolmogorov channel model. However, in [ 25 ], the capacity of the OAM-mmWave communication systems decreased with the increase of the transmission frequency, where the selected transmission frequency range was 100 GHz–300 GHz. We conclude that the selected transmission frequency range has a great influence on the RV communication system based on the PAAR scheme in a turbulent atmospheric environment.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Investigations on how to make such systems robust to practical impairments of multipath, misalignment of orientation, and so on are critical to increase their practical utility. While some preliminary work has been done in that direction, e.g., in multipath propagation [116] and turbulence [117], further work is required. Since OAM performs better with electrically larger antennas, it is better suited for high mmWaves and THz systems and, in particular, for free-space optics applications (see [8] and [118]).…”
Section: B Multiple Antenna Techniquesmentioning
confidence: 99%
“…In this paper, the millimeter wave wireless communication which belongs to the high frequency communication is assumed. So the Kolmogorov turbulent flow is also suitable for wireless communications [18]. Considering the Kolmogorov turbulent flow, the complex phase perturbations e ψ(r,ϕ,z) satisfies [13] e ψ(r,ϕ,z)+ψ * (r,ϕ ,z) = e…”
Section: Phase Distortion Model Of Oam-ofdmmentioning
confidence: 99%
“…Considering (18) and the BER of OAM signals [33], the BER of the OAM-OFDM signals can be expressed as…”
Section: Capacity Model Of Oam-ofdm Transmission Systemsmentioning
confidence: 99%
See 1 more Smart Citation